Feasibility of MR-guided ultrahypofractionated radiotherapy in 5, 2 or 1 fractions for prostate cancer. (January 2021) - Mohajer, Jonathan; Dunlop, Alex; Mitchell, Adam; Goodwin, Edmund; Nill, Simeon; Oelfke, Uwe; Tree, Alison
Highlights: Deliverable plans for 1 and 2 fraction SBRT can be created for the Unity MR-Linac. Dose constraints and objectives from HDR and SBRT clinical studies were applied. In 40% of 1 and 2 fraction plans target doses were compromised to meet OAR goals. Abstract: The drive towards hypofractionated prostate radiotherapy is motivated by a low alpha/beta ratio for prostate cancer (1 to 3 Gy) compared to surrounding organs at risk, implying an improved therapeutic ratio with increasing dose per fraction. Early evidence from studies of ultrahypofractionated (UHF) prostate HDR brachytherapy has shown good tolerability in terms of normal tissue toxicities and clinical outcomes similar to conventional fractionation schedules. MR-guided stereotactic body radiotherapy (SBRT) with online plan adaptation and real-time tumour imaging may enable UHF doses to be delivered to the prostate safely, without the invasiveness of brachytherapy. The feasibility of UHF prostate treatment planning for the Unity MR-Linac (MRL, Elekta AB, Stockholm) was investigated for target prescriptions and planning constraints derived from the HDR brachytherapy and SBRT literature. Monaco 5.40 (Elekta) was used to generate MRL step-and-shoot IMRT plans for three dose fractionation protocols (5, 2 and 1 fractions), for ten randomly selected previously treated prostate cancer patients. Of the ten plans per UHF scheme, all clinical goals were met in all cases for 5 fractions, and in six cases for both 2 and 1 fraction schemes. PTV D95% was compromised by up to 6.4% and 3.9% of the associated target dose for 2 and 1 fraction plans respectively. There were two cases of PTV D95% compromise greater than a 5% dose decrease for the 2 fraction plans. The study suggests feasibility of the UHF treatment planning approaches if combined with real-time motion mitigation strategies.